FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STROKE PADA USIA 15-44 TAHUN Di KLINIK NEUROLOGI RSUD dr SLAMET KABUPATEN GARUT TAHUN 2019 - RAHMAYANI, SRI TANTI (Kos Globalindo Group, 2020)
Stroke is one of the non communicable diseases with the number of patients continues to increase from year to year and stroke begin attack the younger. The purpose of this study to determine the factors associated with stroke in age 15-44 years at the Neorologi Clinic of RSUD dr Slamet Garut Regency. Design of this research is analytic survey method with cross sectional study. The samples obtained were 95 respondents using questionnaires through accidental sampling technique in July 2019. The data obtained and analyzed using univariate and bivariate using Chi-square test with a significant level of Î± â‰¤ 0:05. The results of this research is correlation of smoking with stroke get probability 0,006 (p < 0.05), correlation of sprots with stroke get probability 0,023 (p < 0.05), correlation of hypertension with stroke get probability 0,000 (p < 0.05) and correlation of obesity with stroke get probability 0,020 (p < 0,05). Based on the description above, it advisable to check up regularly every month to check his health so that it can be controlled properly there is recurring stroke or risk of stroke. Keywords: Stroke, Risk Factors, age 15-44 Years